Sources of Stress in Relation to Sleep Health During the COVID-19 Pandemic: Findings from the National Couples’ Health and Time Study - Izabelle Mendez; Rupsha Singh; Chandra L. Jackson; Amanda Hinerman; Erik J. Rodriquez; Emma Martinez; Juliana Teruel Camargo; Eliseo J. Pérez-Stable (Journal of Racial and Ethnic Health Disparities, 2026)
Abstract Objective To assess associations between sources of stress and sleep health among married/cohabitating US adults during the COVID-19 pandemic. Methods We analyzed the National Couples’ Health and Time Study, an online survey completed 2020-2021. Stressors were categorized into five domains––1) COVID-19 infection; 2) resources/insurance; 3) overall health; 4) job/income; and 5) public health recommendations. Sleep quality and duration (